The Effect of Rotating Speed and Working Pressure on the Hydrodynamic and Hydrostatic Pressure Distribution of the Oil Lubrication Film in the Internal Gear Pump - Pham, Trong Hoa (Old Journal, 2020)
The effect of rotating speed and working pressure on the hydrodynamic and hydrostatic pressure distribution of the oil lubrication film in the internal gear pump has been analysed in this paper. The hydrodynamic pressure distribution is calculated based on the Reynolds Equation which is solved by the finite difference method (FDM). Meanwhile, the hydrostatic pressure distribution is computed based on the hydraulic resistance network model. The calculation results pointed out that the rotating speed and working pressure have a great effect on the hydrodynamic and hydrostatic pressure distribution. These results are the background for further study to improve the stability, working efficiency, and lifespan of the internal gear pump.